(untitled) (Journal of the College of Languages (JCL), 2025)
This research explores the various forms of resistance embedded in Dunya Mikhail’s poetry through a feminist lens, focusing on her articulation of women’s struggles against socio-political injustices. Analyzing Mikhail’s poetry alongside critical feminist theory, the study reveals that her work employs nuanced imagery and subversive language to challenge oppressive structures, emphasizing themes of female agency, identity, and resilience. Key findings indicate that Mikhail’s poetry not only critiques the socio-political landscape but also advocates for empowerment and social change, making a vital connection between personal narratives and broader feminist movements. The significance of these insights extends beyond literary analysis, highlighting the importance of creative expression in addressing issues of physical health and emotional well-being, particularly for marginalized voices affected by systemic oppression. Accordingly, this paper offers a new reading of Dunya Mikhail’s poetry in the light of Judith Butler’s theory of gender performativity, suggesting that the former’s female characters challenge societal and cultural limitations to engage in a fluid, performative gender identity that redefines the parameters of feminist representations. Through a reconstructed sense of self, their flaws serve as a catalyst to redefine gender identity, not as a static defect or source of despair, but as an exploratory realm from which new expressions of the self or identity can arise. This paper examines how Mikhail’s poetic portrayal of women embodies feminist resistance via symbolic defiance, fluidity, and nonconformity. By placing Mikhail’s work in the context of feminist theory and post-war sociopolitical dynamics in Iraq, the paper uncovers how gender identity acts as a point of resistance and how poetic language functions as a transformative medium for self-expression.